Triple helix in the management of innovation in public policies: a study of two countries - Tiossi, Fabiano Martin (2023)
This study deals with the Triple Helix development model’s efficient application in managing innovation in public policies in a Brazil-Portugal comparison. The Triple Helix model has its origin in England, to resume the economy in decline and unite the initiatives, until then unilateral, of universities-industries-government. Internationally recognized as a model of innovation and development, Triple Helix uses mechanisms that aim to mitigate the failures existing in universities, industries, and governments, transforming knowledge into practices aimed at the economy and improving the three elements’ interactions. In this sense, the work’s objective is to present how the process of operationalization of public policies aimed at innovation is developed, aligning government, Industry, and universities in a Brazil-Portugal comparison. For its development, bibliographic research and a comparative exploratory study about innovation management in Brazilian and Portuguese public policies were used. As a result, it is confirmed that, with the Triple Helix model in innovation management, public policies focused on science and technology is more effective. Even more, the greater the involvement between the three actors of the development model.